Cubic and rhombohedral Ba4Lu3F17:Er3+ in transparent glass ceramics: Crystallization and upconversion luminescence - Krieke, Guna; Sarakovskis, Anatolijs; Springis, Maris (Elsevier B.V., 2018)
Novel Er3+ doped glass ceramics containing Ba4Lu3F17 nanocrystals were successfully prepared by heat treatment of melt-quenched glasses. Highly efficient upconversion luminescence was detected under near-infrared excitation and it was at least two orders of magnitude higher than that in the precursor glass. The activator content in the crystalline phase was estimated using polycrystalline Ba4Lu3F17 with different Er3+ content as the reference and it was found to be higher than in similar glass ceramics. The structure and thermal analysis of the glass ceramics revealed the formation of cubic and rhombohedrally distorted cubic modifications of Ba4Lu3F17. Phase transition between the two modifications was studied using site selective spectroscopy of Er3+ as a structural probe. Unusually efficient incorporation of Er3+ ions in the Ba4Lu3F17 nanocrystals combined with the low phonon energy of the fluoride crystals make this material a desirable host for upconversion luminescence. ----/ / /---- This is the preprint version of the following article: G. Krieke, A. Sarakovskis, M. Springis, Cubic and rhombohedral Ba4Lu3F17:Er3+ in transparent glass ceramics: Crystallization and upconversion luminescence 200 (2018), which has been published in final form at https://www.sciencedirect.com/science/article/abs/pii/S0022231317322056. This article may be used for non-commercial purposes in accordance with Elsevier Terms and Conditions for Sharing and Self-Archiving. CC BY-NC-ND
CC BY-NC-ND
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Upconversion; Luminescence; Ba4Lu3F17; Site-selective spectroscopy; Glass ceramics